Conexão eleitoral e atuação parlamentar dos vereadores de Fortaleza - Facundo, Leo David Terto (2015)
This argumentative text aimed to investigate how the phenomenon of electoral connection occurs in the production of Legislative Councillors of the Câmara Municipal de Fortaleza (CMF), in the 16th legislature (2009-2012). The work is divided into six chapters. In the second chapter, we raise some historical facts about the training of Municipalities in Brazil and, concomitantly, we analyze the role of the municipality in the Federation, focusing on transformations in its mission, especially after the Constitution of 1988. In the third chapter, we introduce the operation of the Câmara Municipal de Fortaleza and the institutions that make up, having as objective to describe the dynamics of work of this legislative House. In the next chapter, we discussed the concept of electoral connection and analyze historically the municipal elections in Fortaleza, our focus was to identify the relevant political groups acting in the cearense capital after redemocratization. Then we expose General characteristics of the election of 2008 and the candidates elected: context of the dispute, competition and party coalitions. In the fifth chapter, we develop, as methodological tool, a typology for classifying the aldermen. To develop this typification take into account theory about the aldermen, the profile of voting, the voting maps and the relationship with the electoral bases. In this sense, we define the following types: (1) territorial Councillor; (2) Councillor and hierarchical; (3) Councillor ideological. In the next chapter, we present a database on the production of parliamentary Commissioners, justifying the choice of four species specific legislative: ordinary bills, supplementary law projects, projects for amendment to the organic law and guidance. Then, we analyze the legislative production having as dependent variable the three types of Alderman and as independent variables, the species, the legislative reach of propositions and the thematic areas. Finally, we conclude the existence of electoral connection in at least two types, namely, the territorial and ideological. About the tiered type we cannot say for sure that he acts on the basis of electoral bases, since his relationship with voters is toggled and discontinuous. However, we can say that the three types Act in Parliament from separate logics. Despite incentives from the rules of operation of the camera, there is certainly room for a legislative action linked to electoral bases, contrary to part of the polls that point to a connection to the works of foreign electoral legislative proposition.